Advektive Ausbreitung und Zeitskalen der Agulhas Leakage in einem globalen Ozeanmodell - Ruehs, Siren (2011)
To investigate the advective propagation of Agulhas Leakage into the Atlantic Ocean this study evaluates results of the hindcast experiment K326 of the global eddy-permitting ocean model ORCA025. Using the software ARIANE a lagrangian analysis of virtual floats is realized that provides information about the pathways and advective timescales of Indian Ocean water entering the Atlantic. In the period from 1965 to 1974 the modeled mean volume transport is 68,6 Sv for the Agulhas Current and 15,1 Sv for Agulhas Leakage. In general floats of the Agulhas leakage are first advected with the South Equatorial Current. Some of them circulate in the subtropical gyre of the southern hemisphere, but most of them do not reach the North Atlantic during the integration period of 86 years. The majority of the floats that end up in the North Atlantic directly follow the North Brasil Current to equatorial latitudes after their advection with the South Equatorial Current. A large portion of Agulhas Leakage reaches the subtropical North Atlantic in about one decade and accounts for the thermohaline circulation in a non-negligible way. On average there are 10 Sv of Agulhas Leakage passing 6° South and 6 Sv passing 26° North. The most likely timescales associated with the advection up to those latitudes are 6 and 14 years respectively. Agulhas Leakage even penetrates far higher latitudes but it takes several more decades for Leakage floats to get there. During their way into the North Atlantic Floats of the Agulhas Leakage are likely to be affected by the intricate zonal equatorial circulation. Moreover there is a high probability for recirculation in the subtropical gyre of the northern hemisphere. The identified advective timescales become especially relevant under consideration of the latest IPCC results. Based on model simulations, that poorly represent the dynamics of Agulhas Leakage, the IPCC states that a weakening of the MOC during the 21. century is most likely. Keeping in mind previous surveys, the current findings support ...